2010
DOI: 10.1016/j.cellimm.2010.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Differential requirement of lipid rafts for FcγRIIA mediated effector activities

Abstract: Immunoglobulin G (IgG) dependent activities are important in host defense and autoimmune diseases. Various cell types including macrophages and neutrophils contribute to pathogen destruction and tissue damage through binding of IgG to Fcγ receptors (FcγR). One member of this family, FcγRIIA, is a transmembrane glycoprotein known to mediate binding and internalization of IgG-containing targets. FcγRIIA has been observed to translocate into lipids rafts upon binding IgGcontaining targets. We hypothesize that lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…Studies in vitro suggested that PI3K downstream of Fc␥R-mediated endocytosis engages signals necessary specifically for NETosis. Our data (that small soluble ICs with predicted size in the nanometer range 48 leads to NET formation, whereas uptake of the larger IgG-RBC (Ͼ 3.0M) or spreading on ICs does not) suggest that the size of the target and/or IC valency matters. The selectivity of soluble IC uptake for DNA release suggests that distinct Fc␥R-dependent cellular processes trigger NET formation, whereas the occurrence of NETs in the absence of the NADPH oxidase both in vitro and in vivo challenges the paradigm that the oxidative burst is a prerequisite for this process.…”
Section: Fc␥riiib and Fc␥riia Mediate The Clearance Of Ic In Vivomentioning
confidence: 70%
See 1 more Smart Citation
“…Studies in vitro suggested that PI3K downstream of Fc␥R-mediated endocytosis engages signals necessary specifically for NETosis. Our data (that small soluble ICs with predicted size in the nanometer range 48 leads to NET formation, whereas uptake of the larger IgG-RBC (Ͼ 3.0M) or spreading on ICs does not) suggest that the size of the target and/or IC valency matters. The selectivity of soluble IC uptake for DNA release suggests that distinct Fc␥R-dependent cellular processes trigger NET formation, whereas the occurrence of NETs in the absence of the NADPH oxidase both in vitro and in vivo challenges the paradigm that the oxidative burst is a prerequisite for this process.…”
Section: Fc␥riiib and Fc␥riia Mediate The Clearance Of Ic In Vivomentioning
confidence: 70%
“…47 This is consistent with Fc␥RIIIB being a GPI-linked protein present in lipid rafts 8 and the described translocation of Fc␥RIIA to lipid rafts on binding of IgG-containing targets or Fc␥RIIIB crosslinking. 11,48,49 Although both Fc␥RIIA and Fc␥RIIIB share a common endocytic pathway, Fc␥RIIA, but not Fc␥RIIIB, expressed at the same level, promoted the formation of NETs in vivo, a proinflammatory event that contributes to host defense but may also be deleterious to the host as it supports thrombosis and autoimmunity. 29,50 In vitro, the discrepancy between human and mouse studies in Fc␥RIIIB's contribution to NETosis is probably the result of the approaches used to achieve a loss of function of Fc␥RIIA.…”
Section: Fc␥riiib and Fc␥riia Mediate The Clearance Of Ic In Vivomentioning
confidence: 99%
“…To identify the mechanism of phagocytosis of rMVA-induced apoptotic bodies by ALDC, phagocytosis assays were set up as described above in the presence of the following inhibitors, which have been shown to block phagocytosis: cytochalasin D (10 M; actin dependent [65]), fillipin (5 g/ml; caveolae dependent [64]), chlorprozamine (10 g/ml; prevents clathrin-coated-pit formation [78]), methyl-␤-cyclodextrin (10 mM; cholesterol dependent [75]), and amiloride (10 mM; blocks Na ϩ [79] and therefore macropinocytosis [66]). DMSO was used as a diluent control, and PBS was used as a negative control.…”
Section: Infectionmentioning
confidence: 99%
“…The following inhibitors and final concentrations were used to block endocytosis: cytochalasin D [1 µM, actin-dependent (Sakr et al , 2001)]; filipin [5 µg ml −1 caveolae-dependent (Rothberg et al , 1992)]; chlorpromazine [10 µg ml −1 , prevents clathrin-coated pit formation (Wang et al , 1993)]; methyl-β-cyclodextrin [10 mM, cholesterol-dependent (Vieth et al , 2010)]; amiloride [1 mM, Na + blocker (West et al , 1989) and therefore blocks macropinocytosis (Sallusto et al , 1995)]; ciliobrevin [10 µM, inhibitor of motor cytoplasmatic dynein (Firestone et al , 2012); and dynasore [8 mM, inhibitor of dynamin- and clathrin-dependent endocytosis (Macia et al , 2006)].…”
Section: Methodsmentioning
confidence: 99%